Mechanical properties of concrete reinforced with corrugated steel fiber under uniaxial compression and tension. (December 2021) - Ran, Jinlin; Li, Tingchun; Chen, Dianhao; Shang, Liming; Li, Weiteng; Zhu, Qingwen
Abstract: The use of corrugated steel fibers can improve the interface bonding strength between the fiber and the concrete, thereby exhibiting superior mechanical properties of steel fibers reinforced concrete (SFRC). However, the effect of corrugated steel fibers on full-range constitutive behaviors of concrete under uniaxial compression and tension are generally unavailable. Therefore, this paper investigated the effects of fiber volume fraction and concrete matrix strength on the compressive and tensile properties of concrete through experiments conducted on prismatic specimens containing corrugated steel fibers. Test results indicated that the concrete properties improved as both fiber volume fraction and concrete matrix strength increase, and the enhancements in tensile behaviors provided by the corrugated steel fibers were more remarkable compared to compressive behaviors. In addition, a comprehensive comparison with the results obtained from the experimental database confirmed that the corrugated steel fibers appeared to have higher reinforcing effect on concrete properties than the straight and hooked fibers. Finally, based on the composite theory, a modified coefficient of elastic modulus of SFRC was proposed, and new theoretical models were developed for the predictions of compressive strength and tensile strength of SFRC. The proposed models showed a good agreement with the test results.